Incidence of QT interval prolongation in patients receiving bedaquiline for drug-resistant tuberculosis in Sub-Saharan Africa: a protocol for systematic review and meta-analysis - Felix Bongomin; Ronald Olum; Morrish Okello-Obol; Ivaan Pitua; James Nelson Okema; Doris Ekwem (BMJ Open, 2025)
Introduction Tuberculosis (TB) remains a major public health challenge in Sub-Saharan Africa, exacerbated by the high prevalence of drug-resistant TB (DR-TB) and its strong association with HIV. Bedaquiline (BDQ), approved by the WHO in 2013, offers a promising treatment for DR-TB, including multidrug-resistant TB (MDR-TB) and extensively DR-TB (XDR-TB). However, BDQ has been associated with QT interval prolongation, a condition that can lead to serious cardiac arrhythmias such as torsades de pointes. This systematic review and meta-analysis aims to quantify the incidence of QT interval prolongation in patients receiving BDQ for DR-TB in Sub-Saharan Africa and identify predictors of this adverse effect.Methods and analysis We will conduct a comprehensive search of PubMed, Embase, Cochrane Library, Web of Science and African Journals Online using medical subject headings and keywords related to ‘BDQ’, ‘DR-TB’, ‘QT interval prolongation’ and ‘Sub-Saharan Africa’. Eligible studies will include randomised controlled trials, cohort studies, case-control studies and observational studies conducted in Sub-Saharan Africa. Study titles and abstracts will be initially screened, and full texts will be retrieved and reviewed against eligibility criteria. Relevant data will be extracted from the selected articles and assessed for risk of bias. The primary outcome will be the pooled incidence of QT interval prolongation. Data will be synthesised using a random-effects model meta-analysis if significant heterogeneity is present; otherwise, a fixed-effects model will be applied.Ethics and dissemination This study will use published data, requiring no ethical approval. Findings will be disseminated through peer-reviewed publications and conference presentations to inform clinical guidelines and DR-TB treatment policies in Sub-Saharan Africa.PROSPERO registration number CRD42024560368.